Hindu Response to Dying and Death in the Time of COVID-19 - Bilimoria, Purushottama (Frontiers in Psychology, 2021)
We wake each morning to news on the glaring statistics of people infected by COVID-19 and others reportedly dying from complications thereto; the numbers are not receding in at least a number of countries across the world (barring a few that imposed strict lockdowns, testing and quarantining measures, such as Australia, Singapore and New Zealand). It is hard to imagine a moment such as this that most of us have lived through in our life-time; but it is a reality and public challenge that we can neither ignore nor look away from. In what follows I will explore perspectives on death from the Hindu tradition and the kinds of response – and solace or wisdom – afforded by the tradition to the angst and fears evoked by this pandemic situation.